2016
DOI: 10.1155/2016/4264721
|View full text |Cite
|
Sign up to set email alerts
|

Aplasia Cutis Congenita of the Scalp with a Familial Pattern

Abstract: Aplasia Cutis Congenita (ACC) is a condition characterized by congenital absence of skin, usually on the scalp. ACC can occur as an isolated condition or in the presence of other congenital anomalies. Here we describe a case of a 16-day-old baby girl with an isolated ACC of the scalp. Her elder two siblings have been diagnosed with ACC with concomitant cardiac or limb anomalies. The patient was managed conservatively until the defect has formed scar tissue 6 months later.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 26 publications
(45 reference statements)
0
1
0
Order By: Relevance
“…To differentiate ACC from these diagnoses, we need further clinical data on ACC, including demographics, family and obstetric histories, and clinical features such as multiplicity, size, shape, hair collar sign, location, radiologic and therapeutic results. However, most available reports on ACC are case reports or series, and original clinical studies are rarely reported. To address this gap in the literature, we performed the current study to present the clinical data of ACC in Korea.…”
mentioning
confidence: 99%
“…To differentiate ACC from these diagnoses, we need further clinical data on ACC, including demographics, family and obstetric histories, and clinical features such as multiplicity, size, shape, hair collar sign, location, radiologic and therapeutic results. However, most available reports on ACC are case reports or series, and original clinical studies are rarely reported. To address this gap in the literature, we performed the current study to present the clinical data of ACC in Korea.…”
mentioning
confidence: 99%